AN EVALUATION OF FERTILITY CAPABILITY CLASSIFICATION OF MBAMBA SOILS IN YOLA SOUTH LOCAL GOVERNMENT AREA NORTH-EASTERN NIGERIA - Jungudo, Muhammed Bashir; Abdulqadir, Abubakar Sadiq (FUDMA Journal of Sciences, 2025)
Understanding soil fertility capability status is considered as one of the most important tool towards improving and managing soil nutrients for profitable and sustainable farming. This study aimed to evaluates fertility capability classification of Mbamba soils in Yola South Local Government Area North-eastern Nigeria. Three (3) profile pits were dug based on the topo-sequence variation where core soils samples of the soils were collected from the identified distinct horizons. The results revealed that fertility capability classification (FCC) of the soils at profile 1 and 3 was classified as LLdn-km dominated with loamy soil developed under ustic moisture regime having 6-15 % Na saturation, low nutrient reserve and organic matter. In addition, at profile 3 site of the area it was classified as SLdn-km characterized as soil dominated with sandy texture at surface and loamy at subsurface horizons with low nutrient reserve, low exchangeable cation exchange capacity and organic matter content. Generally, the soils were classified as low fertility capability soils to support effective crop growth and development. Therefore, there is ardent need for the farmers in the area to employ integrated nutrients management techniques with the aim of improving and sustaining the soil nutrients for sustainable food production in the area.
Keywords: Capability; Classification; Evaluation; Fertility; Soil